Ion Imprinted Polymers for Selective Recognition and Separation of Lanthanum and Cerium Ions from other Lanthanide - Nik Rohani, Nik Mustapa; Muhammad Nor Fazli, Abd Malek; M. M., Yusoff; Lutfor, M. R. (Taylor, 2016)
The lanthanide-ion-imprinted polymers (L-IIPs) were synthesized from La3+ or Ce3+ ion and complexing agents either Schiff base or azobenzene with ethylene glycol-dimethylacrylate as cross-linking agent, 4-vinylpyridine monomer and 2,2-azobisisobutyronitrile initiator. After polymerization, cavities in the polymer particles corresponding to the La3+/Ce3+ ions were created by leaching in 20 mL of HCl solution (2.0 mol L−1). The maximum sorption capacity is found to be 25.0, 24.3, 24.5 and 24.7 mg g−1 of La-IIP-Schiff, La-IIP-Azo, Ce-IIP-Schiff, Ce-IIP-Azo polymers, respectively at pH 6. The L-IIPs gave good selectivity to La or Ce ions in the presence of other selected lanthanide cations with close atomic radius. The L-IIPs were reused and regenerated for ten times without a significant decrease in binding affinity.